The effect of Cratylia floribunda lectin on renal hemodynamics and ion transport - Alexandre Havt; Ana Maria Sampaio Assreuy; Nilberto Robson Falcão do Nascimento; Manassés Claudino Fonteles; Lívia de Paula Pereira; Sandra Maria Nunes Monteiro; Paulo Sergio Ferreira Barbosa; Kyria Santiago do Nascimento; Benildo Sousa Cavada; Alice Maria Costa Martins; Helena Serra Azul Monteiro (Universidade de São Paulo, 2015)
Lectins have been described as glycoproteins that reversibly and specifically bind to carbohydrates. Legume lectins isolated from the subtribe Diocleinae (Canavalia, Dioclea andCratylia) are structurally homologous with respect to their primary structures. The Diocleinae lectins of Canavalia brasiliensis, Dioclea guianensis andCanavalia ensiformis have been shown to distinctly alter physiological parameters in isolated rat kidneys. Thus, the aim of this study was to investigate the effect of Cratylia floribunda lectin (CFL) on renal hemodynamics and ion transport in rats. In isolated perfused kidneys, CFL (10 mg/mL, n=5) increased RPP, RVR and decreased %TK+, but did not change urinary flow, glomerular filtration rate, sodium or chloride tubular transport. In isolated perfused mesenteric bed, CFL (3 and 10 mg/mL/min; n=4) did not alter tissue basal tonus or tissue contraction by phenylephrine (1 mM/mL/min). In conclusion, the seed lectin of Cratylia floribunda increased renal hemodynamic parameters showing a kaliuretic effect. This effect could be of tubular origin, rather than a result from haemodynamic alterations.